Additions to the knowledge of Encyrtidae (Hymenoptera: Chalcidoidea) from Norway, with descriptions of two new species - Japoshvili, George; Staverløkk, Arnstein (Zootaxa, 2024)
Two genera of Encyrtidae (Hymenoptera: Chalcidoidea) are for the first time recorded from Norway: Dusmetia Mercet, 1921 and Prionomastix Mayr, 1876. Six new species records for the country are presented, including two newly described taxa: Aphycus staverlokki Japoshvili sp. n. and Metaphycus sannes Japoshvili sp. n. The total number of known Norwegian species of the family is currently 156.